Inhibition of hippocampal long-term potentiation by high-fat diets: is it related to an effect of palmitic acid involving glycogen synthase kinase-3?. Issue 6 (12th April 2017) - Contreras, Ana; Del Rio, Danila; Martínez, Ana; Gil, Carmen; Morales, Lidia; Ruiz-Gayo, Mariano; Del Olmo, Nuria
Abstract : High-fat diets (HFD) impair hippocampal-dependent learning and memory and produce important changes in synaptic transmission by enhancing glutamate uptake, decreasing synaptic efficacy, and inhibiting plasticity mechanisms such as N -methyl-D-aspartate-mediated long-term depression (LTD) within the hippocampus. Adolescent animals seem to be particularly susceptible to the detrimental effect of HFD as dietary treatments carried out between weaning and early adulthood are much more efficient in terms of hippocampal damage that those carried out during the adult period. As palmitic acid is the most abundant saturated fatty acid in HFD, its effect on hippocampal function needs to be studied. However, glycogen synthase kinase-3 (GSK-3), a pleiotropic enzyme highly expressed in the central nervous system, modulates both hippocampal long-term potentiation (LTP) and LTD, and has been implicated in neurological disorders including Alzheimer's disease. In this study, we have characterized in mice hippocampus the effect of (i) a 48 h HFD intervention and (ii) in-vitro palmitic acid, as well as the possible involvement of GSK-3 in the above-mentioned plasticity mechanisms. Our results show that both 48 h HFD and palmitic acid inhibit LTP in hippocampal slices, whereas no effect on LTD was observed. Moreover, tideglusib, an ATP-noncompetitive inhibitor of GSK-3, induced hippocampal LTP and partially reversed the impairment of LTP induced by palmitic acid.